Physicochemical and sorption characteristics of Malaysian Ceiba pentandra (L.) Gaertn. as a natural oil sorbent - Abdullah, MA (2010)
Ceiba pentandra (L.) Gaertn (kapok) is a natural sorbent that exhibits excellent hydrophobic–oleophilic characteristics. The effect of packing density, the oil types and solvent treatment on the sorption characteristics of kapok was studied in a batch system. Oil sorption capacity, retention capacity, entrapment stability and kapok reusability were evaluated. Based on SEM and FTIR analyses, kapok fiber was shown to be a lignocellulosic material with hydrophobic waxy coating over the hollow structures. Higher packing density at 0.08 g/ml showed lower sorption capacity, but higher percentage of dynamic oil retention, with only 1% of oil drained out from the test cell. Kapok remained stable after fifteen cycles of reuse with only 30% of sorption capacity reduction. The oil entrapment stability at 0.08 g/ml packing was high with more than 90% of diesel and used engine oil retained after horizontal shaking. After 8 h of chloroform and alkali treatment, 2.1% and 26.3% reduction in sorption capacity were observed, respectively, as compared to the raw kapok. The rigid hollow structure was reduced to flattened-like structure after alkali treatment, though no major structural difference was observed after chloroform treatment. Malaysian kapok has shown great potential as an effective natural oil sorbent, owing to high sorption and retention capacity, structural stability and high reusability.